The role of cetuximab in converting initially unresectable colorectal cancer liver metastases for resection. Issue 11 (November 2017) - Poston, G.; Adam, R.; Xu, J.; Byrne, B.; Esser, R.; Malik, H.; Wasan, H.; Xu, J.
Abstract: In patients with metastatic colorectal cancer (mCRC) predominantly confined to the liver, whether a patient undergoes potentially curative resection of the liver lesions is a well-established principal determinant of long-term survival. There are a number of different agents, both chemotherapeutic and targeted biologic agents, which can aid in shrinking liver tumors, which would have otherwise been unresectable, allowing for potentially curative resection. The aim of this review article is to summarize the available evidence regarding optimal therapeutic strategies for converting initially unresectable metastases for potentially curative resection; we do not discuss patients who present with initially resectable disease. We have taken the approach to review trials that included R0 resection rates as one of the principal study endpoints and specifically enrolled patients with liver-limited disease. Primary tumor location has recently emerged as a putative prognostic and predictive factor in patients with mCRC; however, presently, there is a lack of resectability outcomes differentiating tumor location–defined subgroups, and several ongoing trials and retrospective analyses are anticipated to guide insights in the future. In conclusion, in patients with RAS wild-type mCRC, the data support preferential use of the anti-epidermal growth factor receptor monoclonal antibody cetuximab when combined with standard-of-care infusional doublet chemotherapy regimens (FOLFOX or FOLFIRI) for the conversion of initially unresectable metastases for potentially curative resection. Furthermore, we discuss data involving intensified chemotherapy regimens (i.e., 3-drug backbones such as FOLFOXIRI with or without a targeted biologic agent) to promote the conversion of initially unresectable metastases for potentially curative resection.